English for Young Learners: Sosialisasi Pentingnya Belajar Bahasa Inggris Sejak Dini di Tingkat Sekolah Dasar - Magfirah, Sulmi; Irsyadi, Hudan; Fajrhi, Nur (LPPM Universitas Bumigora, 2023)
English is a foreign language in Indonesia. Learning English at the elementary school level means equalizing the country’s education quality. English as an international language should be a skill that every student should have. Foreign language learning methods usually used in schools are less effective, where the teacher's role is only to explain without any other actions that can attract students' interest and curiosity in learning. Therefore, teachers must be able to use methods or techniques that are appropriate and more interesting so that elementary school students, who incidentally are children, can enjoy the learning process more and process the content of the material properly. The service team will carry out work programs that can positively impact the teaching-learning environment, namely implementing English for Fun in learning English at the elementary school level. This activity aims to teach elementary school students the importance of learning English from an early age. Apart from that, to introduce them to what English is and how it is used, of course, in the right way. The socialization of learning English at the elementary school level is expected so that students can understand English early and play an active role in the learning process.